2016
DOI: 10.5397/cise.2016.19.4.237
|View full text |Cite
|
Sign up to set email alerts
|

New Retear Pattern after Rotator Cuff Repair at Previous Intact Portion of Rotator Cuff

Abstract: Retear patterns after arthroscopic rotator cuff repair are classified into two patterns according to retear location. Type 1 is when the retear pattern occurs directly on the tendon at the bone repair site using the suture anchor repair method. Type 2 is when the retear pattern occurs at the musculocutaneous junction with a healed footprint in patients who undergo the suture bridge method. Here, the authors report another retear pattern, which was identified as a type 2 retear on magnetic resonance imaging in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In accordance with Cho et al [ 12 ], the retear pattern was classified as type 1 when no rotator cuff tissue was visible in the rotator cuff footprint and as type 2 when remnant cuff tissue was present. The retear was classified as “extra only” if the retear did not affect the previous surgical area [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with Cho et al [ 12 ], the retear pattern was classified as type 1 when no rotator cuff tissue was visible in the rotator cuff footprint and as type 2 when remnant cuff tissue was present. The retear was classified as “extra only” if the retear did not affect the previous surgical area [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, it has both stability and mobility1 ) . Rotator cuff muscles facilitate smooth motions, performing abduction, and rotation, and generates compressive force in the glenohumeral joint2 ) , Mechanical damage of the rotator cuff muscles can be shown by characteristics such as displacement of the shoulder joint, rotation, formation, tendon sprain, tendon movement, fluid outflow, and failure of energy conservation3 ) . It is reported that tendon rupture of the supraspinatus has the highest incidence among rotator cuff muscle injuries4 ) .…”
Section: Introductionmentioning
confidence: 99%